Constructivist Referents in Oumar Farouk Sesay’s ‘The Song of the Women of My Land’ - Thulla, Philip Foday Yamba; Fofanah, Ibrahim Mustapha (Elsya : Journal of English Language Studies, 2023)
The purpose of the research was to examine the constructivist referents in Oumar Farouk Sesay’s poem ‘The Song of the Women of My Land’. This required an analysis and understanding of the referents (terms that clearly and indirectly refer to persons, things or events) and whether the referents were used in the poem to express grief by women. The research questions were as follows: a) Does the poet use referents that suggest the death of traditions that celebrate old women, song bards, and songs from the past more than any other word? b) Is the poet more likely to employ poetic allusions to indicate negative constructivism? and c) Is the poem’s use of prosodic features related to the message? This study used computational and content analysis methods, which incorporate a careful poetry-reading critical approach, to identify and calculate constructivist referents. The referents were then manually broad-coded to include whole lines and verses. The exact words, phrases, and sentences related to the topic were coded and their frequency was determined. These were calculated by counting the number of times a referent appeared. The themes were then selected and interpreted, with a focus on relating them to the poem’s constructivist viewpoint. Finally, the main prosodic elements of the poem, as well as the referents that create them, were established. The results show that most referents by African poets are used to emphasise that traditional culture is dying and that the referents romanticise the fleeting nature of beauty in poetry and the pacifying effects of rural pastimes.